Designing with community health workers: feedback-integrated multimedia learning for rural community health - Molapo, Maletsabisa (Faculty Science: ICTC4D, 2018)
Community Health Workers (CHWs) are an integral part of the rural health system, and it is imperative that their voices are accommodated in digital health projects. In the mobile health education project discussed in this thesis (The Bophelo Haeso project), we sought to find ways to amplify CHWs' voices, enabling them to directly influence design and research processes as well as technological outcomes. The Bophelo Haeso (BH) project equips CHWs with health videos on their mobile phones to use for educating and counselling the rural public. We investigated how to best co-design, with CHWs, a feedback mechanism atop the basic BH health education model, thus enabling their voices in the design process and in the process of community education. This thesis chronicles this inclusive design and research process - a 30-month process that spanned three sub-studies: an 18-month process to co-design the feedback mechanism with CHWs, a 12-month deployment study of the feedback mechanism and, overlapping with the feedback deployment study, a 17-month study looking at the consumption patterns of the BH educational videos. This work contributes to the field of Human Computer Interaction (HCI) in three distinct ways. First, it contributes to the growing knowledge of co-design practice with participants of limited digital experience by introducing a concept we termed co-design readiness. We designed and deployed explorative artefacts and found that by giving CHWs increased technical, contextual, and linguistic capacity to contribute to the design process, they were empowered to unleash their innate creativity, which in turn led to more appropriate and highly-adopted solutions. Secondly, we demonstrate the efficacy of incorporating an effective village-to-clinic feedback mechanism in digital health education programs. We employed two approaches to feedback - asynchronous voice and roleplaying techniques. Both approaches illustrate the combined benefits of implementing creative methods for effective human-to-technology and human-tohuman communication in ways that enable new forms of expression. Finally, based on our longitudinal study of video consumption, we provide empirical evidence of offline video consumption trends in health education settings. We present qualitative and quantitative analyses of video-use patterns as influenced by the CHWs' ways of being and working. Through these analyses, we describe CHWs and their work practices in depth. In addition to the three main contributions, this thesis concludes with critical reflections from the lessons and experiences of the 30-month study. We discuss the introduction of smartphones in rural villages, especially among elderly, low-literate, and non-English-speaking users, and present guidelines for designing relevant and usable smartphones for these populations. The author also reflects on her position as an African-born qualitative researcher in Africa, and how her positionality affected the outcomes of this research.